Role of exosomal microRNAs in lung cancer biology and clinical applications. (11th May 2020) - Hu, Chengping; Meiners, Silke; Lukas, Christina; Stathopoulos, Georgios T.; Chen, Jie
Abstract: Exosomes, small extracellular vesicles ranging from 30 to 150 nm, are secreted by various cell types, including tumour cells. Recently, microRNAs (miRNAs) were identified to be encapsulated and hence protected from degradation within exosomes. These exosomal miRNAs can be horizontally transferred to target cells, in which they subsequently modulate biological processes. Increasing evidence indicates that exosomal miRNAs play a critical role in modifying the microenvironment of lung cancers, possibly facilitating progression, invasion, angiogenesis, metastasis and drug resistance. In this review, we summarize the novel findings on exosomal miRNA functions during lung cancer initiation and progression. In addition, we highlight their potential role and challenges as biomarkers in lung cancer diagnosis, prognosis and drug resistance and as therapeutic agents.